A New Wave of Amide Bond Formations for Peptide Synthesis - Hollanders, Karlijn; Maes, Bert U. W.; Ballet, Steven (Synthesis, 2019)
The construction of peptidic amide bonds has become a daily laboratory practice by virtue of well-established ‘coupling reagents’. Nonetheless, inherent limitations connected to these classical coupling methods in terms of waste, safety and expense have yet to be conquered. Research efforts have been devoted to synthetic methods able to surpass these limitations. This short review focuses on the advances made in these ‘non-classical’ methods for amide bond formation with a specific application in peptide chemistry. It consists of two main sections: (i) novel carboxylic activation reagents, and (ii) carboxylic acid and amine surrogates.1 Introduction2 Alternative Carboxylic acid Activation Reagents3 Carboxylic Acid and Amine Surrogates4 Conclusion and Perspectives
Keywords: amides; peptides; amino acids; non-classical peptide couplings; carboxylic acid surrogates; amine surrogates